Pengembangan Mechanic Court Wasit Bolabasket Menggunakan Animasi Untuk Wasit Tingkat Dasar di Jawa Tengah (Universitas Negeri Semarang, 2023)
The problem in this research is how the development of mechanic court using animation for basic level Basketball Referee in Central Java. Through this research, the author aims to produce a product through the development of the mechanic court of basketball referees using animation for the basic level in Central Java. This study uses a development research method, namely: (1) preliminary research, information gathering and needs analysis, (2) initial product development, (3) evaluation of 2 basketball refereeing experts and 1 animation expert, (4) small group trials (10 samples), (5) first product revision, (6) large group trial (20 samples), (7) final product revision, (8) video script formulation, (9) final product in the form of animated video. The research instruments included evaluation sheets, questionnaires, and documentation. The result of the expert evaluation questionnaire before the small group trial was 77% (Very Good), the small group trial was 97% (Very Good), the expert evaluation questionnaire after the small group trial was 91% (Very Good), the large group trial was 97% (very good). Based on the results of this study concluded that the development of mechanic court referee basketball use animation to the base rate in Central Java is very good for learning as well as the upgrading of refereeing basketball. Researchers hope the product development results are useful for referees, especially to the referee level basic as an effective and efficient learning media.